2010
DOI: 10.1007/s00268-010-0828-2
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Outcome of Hirschsprung’s Disease Presenting after 1 Year of Age in a Developing Country

Abstract: Hirschsprung's disease presenting after 1 year of age may be associated with high colostomy rates and increased morbidity. Continued dissemination of updated information on HD to medical practitioners and a public awareness campaign may improve time to diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 19 publications
4
49
3
2
Order By: Relevance
“…This study showed that males were more affected than females with a male to female ratio of 3.6:1 which is comparable to the global ratio of 2.9: 1 to 4.5: 1 [8-10,12,21]. However, an exceptionally high male to female ratio of 22.3: 1 was reported by Ziad et al .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study showed that males were more affected than females with a male to female ratio of 3.6:1 which is comparable to the global ratio of 2.9: 1 to 4.5: 1 [8-10,12,21]. However, an exceptionally high male to female ratio of 22.3: 1 was reported by Ziad et al .…”
Section: Discussionsupporting
confidence: 78%
“…Ignorance and poverty on the part of the parents, late presentation with attendant complications, limited access to trained paediatric surgeons and limitation of facilities for prompt diagnosis characterize management of this disease. Hence, multiple stages of management still predominate in sub Saharan Africa [7,8,11,12,21]. …”
Section: Introductionmentioning
confidence: 99%
“…[5] The challenges in the developing world is delayed presentation with cases presenting late in childhood, adolescence or even in adults. [6,7] This survey revealed that only about 20% of the HD is seen by the respondents in the neonatal period. The reasons for the delayed presentation in one report included illiteracy, ignorance, inadequate access to specialised centres, poverty and long distances to travel for medical help.…”
Section: Discussionmentioning
confidence: 95%
“…[2] In developing countries, where access to medical care may be hampered by poverty, poor transportation, and communication systems, the implementation of single-stage repair has made it easier to provide quality care to children with HD. [6,7,29] A survey of the BAPS in 1998 revealed that 41% of the pull through procedures performed at that time were through primary approach. [30] A recent survey of BAPS members by Bradnock and Walker revealed that 86% of 36 respondents now performed primary pull through in a well-child.…”
Section: Discussionmentioning
confidence: 99%
“…Babies who had unrestricted access to AC had a better chance to have their HD diagnosed earlier, had less frequent procedures, and were more likely to avoid a stoma. In other words, this difference in access could be responsible, among other factors, for the delay in patient presentation, which is likely to prolong the child's and the parent's suffering, while increasing the risk of HD-related morbidities [20]. The wide variability in the age at presentation has been reported in a larger series of HD cases [1,16,21]; however, the role of access to care as a cause of such variability has not been explored before.…”
Section: Discussionmentioning
confidence: 97%